Improving Speaking Skills Through The Paired Storyy Telling Model - herdianti, Dewi; Usman, Asep Tutun; Nugraha, Fajar (Cahaya Smart Nusantara, 2023)
The purpose of this study is to find out how it affects and determines the improvement of students' speaking skills after using the cooverative type paired story telling learning model. The design used in this study is one group with a pre-experimental design, where this research is carried out in one class. The instruments used in this study were to take data in the form of observation sheets, oral and written tests to measure students' speaking skills. The data was returned twice, before and after the treatment, to see the improvement of the students' speaking skills. The results of this study stated that the speaking skills after applying the cooverative type paired story telling model were declared to be very good with the acquisition from the first and second observation sheets with a score of 86.8. The results of the hypothesis test of students' speaking ability which can be proven by the sig. (2-tailed) is smaller than significant (0.00 < 0.05) and the calculated t value is greater than the t table (15.56 > 2.201) then Ha is accepted. Which means that there is an increase in speaking skills in using storytelling.